Pandemi Covid 19 Ditinjau Dari Teologi Biblika Untuk Pengabdian Masyarakat - Fitresia, Debora Dian; Jayadi, Lionarto Erson; Phang, Steven (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2021)
Covid 19 is now a problem and a pandemic around the world. This pandemic not only has an impact on the health aspect, but also has a negative impact on the economic, political and other aspects. Seeing this, this article aims to understand the meaning of the Covid 19 pandemic, which is viewed from the aspect of biblical theology. The method used is a descriptive biblical approach. The result of this writing is that Covid 19 is part of the problems faced by every human being and thus humans are challenged to find solutions and reflect on what has happened. In another context, Pandemic 19 is a human effort to return to hope for help and humans with God's help struggle to overcome it, and humans reorient life goals that are not self-centered, but maintain all of God's creations that He has given. Covid 19 sekarang ini menjadi persoalan dan pandemi di seluruh dunia. Pandemi ini tidka hanya berdampak pada aspek kesehatan, tetapi juga berdampak negatif pada aspek ekonomi, politik, dan lainnya. Melihat hal tersebut artikel ini bertujuan untuk memahami makna pandemic Covid 19 yang hal tersebut ditinjau dari aspek teologi biblika. Metode yang digunakan adalah pendekatan biblika deskriptif. Hasil dari penulisan ini adalah Covid 19 merupakan bagian problematika yang dihadapi setiap manusia dan dengan demikian manusia ditantang untuk mencari solusi dan merefleksikan diri apa yang telah terjadi. Pada konteks lain, Pandemi 19 merupakan usaha manusia untuk kembali berharap pada pertolongan dan manusia dengan pertolongan Tuhan berjuang mengatasinya, serta manusia me-reorientasi-kan tujuan hidup yang tidak berpusat pada diri, tetapi memelihara seluruh ciptaan Tuhan yang telah diberikan-Nya.